Review of Calauta Solovyev & Witt, 2009 (Lepidoptera: Limacodidae) with description of a new species from Korea - Sohn, Jae-Cheon; Solovyev, Alexey V. (Zootaxa, 2022)
The genus Calauta Solovyev & Witt, 2009 is reviewed with four included species. It is critically compared to other similar genera in Limacodidae based on external and genital morphology. A new species, Calauta koreana sp. nov. is described from the Republic of Korea. A taxonomic transfer of Aphendala notoseusa Wu, 2020 to Calauta is proposed. A distributional range of C. obscura Solovyev, 2017 is expanded with new distributional data. A diagnostic key of all the congeners is given. Photographs of habitus and genitalia are provided for all four species of Calauta.